Pelaksanaan Strategi Thinking Aloud Pairs Problem Solving (TAPPS) untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa Kelas XI IPA 1 MAN 2 Pesisir Selatan pada Materi Limit Fungsi Aljabar - Artita Salmi (Journal on Education, 2022)
This research is motivated by the fact that students do not understand the concept well so that they have difficulty in applying the concept to solve problems, interest and student learning activities to learn mathematics are still very low, some students think that mathematics is one of the subjects that are considered difficult and less liked students, most students feel ashamed to ask the teacher about the material they do not understand, and the low learning outcomes obtained by students and have not met the KKM set, which is 80. The purpose of this study is to describe efforts to increase activity and learning outcomes of class XI IPA 1 MAN 2 Pesisir Selatan academic year 2017/2018 during the teaching and learning process of Mathematics through the implementation of the TAPPS strategy in the Limit Function Algebra material. The action hypothesis is that there is an increase in the activities and learning outcomes of class XI IPA 1 MAN 2 Pesisir Selatan academic year 2017/2018 during the teaching and learning process of Mathematics through the implementation of the TAPPS strategy in the Limit Function Algebra material. The subjects in this study were students of class XI IPA 1 MAN 2 Pesisir Selatan for the academic year 2017/2018, totaling 32 people. This study consisted of two cycles, each of which consisted of three meetings. The percentage of completeness in cycle 1 was 71.87% with an average of 79.63. The percentage of completeness in cycle 2 was 96.88% with an average of 88.13. Student learning activities also showed a significant increase in each indicator.